Case Report: Two Novel Frameshift Mutations in SLC20A2 and One Novel Splice Donor Mutation in PDGFB Associated With Primary Familial Brain Calcification - Shen, Yuqi; Shu, Shi; Ren, Yaqiong; Xia, Weibo; Chen, Jianhua; Dong, Liling; Ge, Haijun; Fan, Shiqi; Shi, Lei; Peng, Bin; Zhang, Xue (Frontiers in Genetics, 2021)
Primary familial brain calcification (PFBC, OMIM#213600), also known as Fahr’s disease, is characterized by bilateral and symmetric brain calcification in the basal ganglia (globus pallidus, caudate nucleus, and putamen), thalamus, subcortical white matter, and cerebellum. PFBC can be caused by loss-of-function mutations in any of the six causative genes. The most common clinical manifestations include movement disorders, cognitive impairments, and neuropsychiatric signs that gradually emerge in the middle-age of patients. To broaden the PFBC mutation spectrum, we examined nine members of a family having PFBC and two sporadic cases from clinical departments and sequenced all PFBC-causative genes in the index case. Two novel frameshift mutations in SLC20A2 [NM_001257180.2; c.806delC, p.(Pro269Glnfs*49) and c.1154delG, p.(Ser385Ilefs*70)] and one novel splice donor site mutation (NM_002608.4, c.456+1G>C, r.436_456del) in PDGFB were identified in the patient cohort. c.806delC co-segregated with brain calcification and led to SLC20A2 haploinsufficiency among the affected family members. The c.456+1G>C mutation in PDGFB resulted in aberrant mRNA splicing, thereby forming mature transcript containing an in-frame 21 base pair (bp) deletion, which might create a stably truncated protein [p.(Val146_Gln152del)] and exert a dominant negative effect on wild-type PDGFB. All three mutations were located in highly conserved regions among multiple species and predicted to be pathogenic, as evaluated by at least eight common genetic variation scoring systems. This study identified three novel mutations in SLC20A2 and PDGFB, which has broadened and enriched the PFBC mutation spectrum.